2015
DOI: 10.1021/acsami.5b07462
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Magnetoelectric Coupling in BaTiO3:Fe113 ppm Nanoscopic Segregations

Abstract: We report polycrystalline BaTiO3 with cooperative magnetization behavior associated with the scarce presence of about 113 atomic ppm of Fe ions, clearly displaying magnetoelectric coupling with significant changes in magnetization (up to ΔM/M ≈ 32%) at the ferroelectric transitions. We find that Fe ions are segregated mostly at the interfaces between grain boundaries and an Fe-rich phase, forming a self-composite with high magnetoelectric coupling above room temperature. We compare our results with ab initio c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that Cr, Mn, Fe and Ni are the most suitable TM ions to effectively induce magnetism in BaTiO 3 [2,[25][26][27][28][29][30]. Recently, significant efforts were directed to the Fe-doped BT system, where the focus was towards understanding the structural, ferroelectric and magnetic properties of both bulk and thin films [26,[30][31][32][33][34][35][36]. For instance, Maikhuri et al have investigated the ferroelectric and magnetic properties of 10 at% Fe substitution at both Ba-and Ti-site, respectively, in BaTiO 3 and revealed the multiferroic nature in both the cases [36].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Cr, Mn, Fe and Ni are the most suitable TM ions to effectively induce magnetism in BaTiO 3 [2,[25][26][27][28][29][30]. Recently, significant efforts were directed to the Fe-doped BT system, where the focus was towards understanding the structural, ferroelectric and magnetic properties of both bulk and thin films [26,[30][31][32][33][34][35][36]. For instance, Maikhuri et al have investigated the ferroelectric and magnetic properties of 10 at% Fe substitution at both Ba-and Ti-site, respectively, in BaTiO 3 and revealed the multiferroic nature in both the cases [36].…”
Section: Introductionmentioning
confidence: 99%
“…Heterostructures containing BaTiO 3 (BTO) and/or Fe phases have been widely studied since these materials are individually competitive, non-critic and inexpensive ferroelectric and ferromagnetic materials, respectively. These heterostructures can present several magnetoelectric effects depending on the interfaces and conditions assumed/used in the reported studies, thus it is expectable that the synthesis conditions and/or substrates can be used as a means of tuning the electric, magnetic and magnetoelectric properties of these heterostructures [10,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much efforts have focused on extrinsic ME coupling through articial multiferroic heterostructures, such as ferroelectric (FE)/ferromagnetic (FM) interfaces. [15][16][17] In addition to the common way to engineer ME coupling through strain, 18 interface bonding and the spindependent screening mechanisms are other two important extrinsic coupling mechanisms. In the interface bonding mechanism, the interfacial atomic displacements change when polarization is reversed, which alters the chemical bondings and the orbital hybridizations at the interface, and hence affecting the interface magnetization.…”
Section: Introductionmentioning
confidence: 99%